A compact open-hole compression test fixture for composite materials. (15th October 2021) - Yu, Su; Colton, Jonathan S.
Abstract: A new open-hole compression (OHC) test fixture for composite laminates is proposed as a promising alternative to existing test fixtures. It is tested on both standard angle (SA) and non-standard angle (NSA) laminates. As compared to ASTM D6484, the new test fixture increases the fiber continuity threshold from 17° to 27° (which is required for accurate testing of NSA), with 80% less material needed for coupons. The new fixture shows results consistent with ASTM D6484 on SA laminates, but are significantly different OHC strengths (up to 28%) on NSA laminates. The difference on NSA laminates may be due to the 17° fiber continuity threshold in ASTM D6484, suggesting a potential application of the proposed fixture in NSA studies. From this preliminary testing with NSA laminates, fiber continuity could be a critical factor for the laminate to benefit OHC strength improvement from flipped angle designs. Highlights: Fixture increases fiber continuity threshold for ply angles from 17° for ASTM D6484 Fixture reduces material consumption by 80% Flipped angle designs increase OHC strength